The accumulation of the basic domain of HIV-1 Tat protein in the nuclei and the nucleoli is different from the accumulation of full-length Tat proteins - Musinova, Y.R.; Sheval, E.V. (Вiopolymers and Cell, 2015)
Aim. Protein fragments coding for nuclear (NLS) and/or nucleolar (NoLS) localization signals are often used for the investigation of the mechanisms of protein accumulation inside the nuclei and the nucleoli, but it is possible that accumulation mechanisms in full-length proteins will be different. Methods. Here, we compared the nuclear and nucleolar accumulation of HIV-1 Tat protein and its basic domain containing both NLS and NoLS. Results. The pattern of accumulation of the basic domain of HIV-1 Tat protein in the nuclei and the nucleoli is different from that of full-length Tat proteins: the basic domain is accumulated weaker inside the nuclei, but stronger in the nucleoli as compared to the full-length protein. Conclusion. The molecular mechanism of nuclear and nucleolar accumulation of full-length Tat protein might be different from that of the Tat protein fragments. Мета. При вивченні механізмів накопичення білків в ядрі і полісом часто використовують фрагменти білка, що кодують сигнали ядерної (NLS) і ядерцевої (NoLS) локалізації, які зливають з маркерними білками. Проте механізми накопичення повнорозмірних білків можуть бути іншими. Методи. У цій роботі ми порівняли накопичення в ядрі і полісом ВІЛ-1 Tat білка і основного домену цього білка, що містить NLS і NoLS. Результати. Показано, що накопичення основного домену Tat білка в ядрі і полісом відрізняється від накопичення цілих білків (фрагмент білка гірше, ніж цілий білок накопичується в ядрі, але краще в полісом). Висновки. Видається ймовірним, що молекулярний механізм накопичення в ядрі і полісом повнорозмірного Тат білка можуть відрізнятися від механізму, описаного з використанням фрагментів білка. Цель. При изучении механизмов накопления белков в ядре и ядрышке часто используют участки белка, кодирующие сигналы ядерной (NLS) и ядрышковой (NoLS) локализации, которые сливают с маркерными белками. Однако механизмы накопления полноразмерных белков могут быть другими. Методы. В настоящей работе мы сравнили накопление в ядре и ядрышке HIV-1 Tat белка и основного домена этого белка, содержащего NLS и NoLS. Результаты. Показано, что накопление основного домена Tat белка в ядре и ядрышке отличается от накопления целых белков (фрагмент белка хуже, чем целый белок накапливается в ядре, но лучше в ядрышке). Выводы. Представляется вероятным, что молекулярный механизм накопления в ядре и ядрышке полноразмерного Tat белка могут отличаться от механизма, описанного с использованием фрагментов белка.